Quartz glass crucible for pulling up silicon single crystal and method for producing silicon single crystal using quartz glass crucible for pulling up silicon single crystal
By forming a semi-melting layer on the outer surface of the quartz glass crucible and increasing the density of the through holes, the problem of insufficient durability of the crucible is solved, and the effect of maintaining high temperature stability and high-quality growth of single crystal silicon in a long-term crystal lifting process is achieved.
Patent Information
- Application Number
- CN202380075061.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-10-25
- Filing Date
- 2023-09-19
- Publication Date
- 2025-06-06
AI Technical Summary
The existing quartz glass crucibles are insufficient in the long-term crystal lifting process, and are prone to deformation, and cannot effectively improve the durability of the crucible.
By forming a semi-melting layer on the outer surface of the quartz glass crucible, a plurality of depressions with a diameter of more than 0.2 mm and less than 5.0 mm are formed on the surface thereof, partial depressions penetrate to the crucible body to form a through hole, thereby increasing the crystallization speed of the outer surface of the crucible and the thickness of the crystal layer.
The durability of the crucible at high temperature is improved, and it can withstand long-term crystal lifting processes to ensure high-quality growth of single crystal silicon.
Smart Images

Figure CN120112683A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a quartz glass crucible for pulling single crystal silicon and a method for manufacturing the same, and also to a method for manufacturing single crystal silicon using the quartz glass crucible. Background Art
[0002] In the manufacture of single crystal silicon based on the Czochralski method (CZ method), a quartz glass crucible (silica glass crucible) is used. The CZ method is to melt polycrystalline silicon raw materials in a quartz glass crucible to generate a silicon melt, immerse a seed crystal in the silicon melt, rotate the quartz glass crucible and the seed crystal, and slowly pull the seed crystal, thereby growing a larger single crystal at the lower end of the seed crystal. According to the CZ method, the yield of large-diameter single crystal silicon can be improved.
[0003] The quartz glass crucible is a silica glass container that holds the silicon melt in the single crystal silicon pulling process. The inner part (inner layer) of the quartz glass crucible is formed of a transparent glass layer that substantially does not contain bubbles because it is in contact with the silicon melt, and the outer part (outer layer) is formed of a bubble-containing layer containing a large number of bubbles in order to disperse the radiation heat from the outside and evenly heat the inside of the crucible.
[0004] As a method for manufacturing a quartz glass crucible, a rotating mold method is known. This manufacturing method is a method for manufacturing a crucible by heating quartz powder deposited on the inner surface of a rotating mold from the center side of the mold to vitrify it, and during melting, air in the quartz powder deposited layer is sucked from the mold side to remove bubbles in the glass layer, thereby forming a transparent glass layer inside the crucible.
[0005] Regarding a quartz glass crucible, for example, Patent Document 1 describes a quartz glass crucible and a method for manufacturing the same, wherein the outer surface roughness of the lower portion to the R portion of the straight body portion formed as an opaque outer layer is greater than the outer surface roughness of the upper portion to the middle portion of the straight body portion and greater than the outer surface roughness of the bottom portion. The outer surface roughness of the upper portion to the middle portion of the straight body portion is 5 μm or more and 50 μm or less, whereas the outer surface roughness of the lower portion to the R portion of the straight body portion is 30 μm or more and 100 μm or less.
[0006] In addition, Patent Document 2 describes a quartz glass crucible comprising: an outer surface layer formed of a quartz glass layer containing bubbles; an inner surface layer formed of a quartz glass layer in which bubbles are not observed with the naked eye; and a semi-molten quartz layer formed on the surface of the outer surface layer and formed of an unmolten or semi-molten quartz layer, wherein the center line average roughness (Ra) of the semi-molten quartz layer is 50 μm to 200 μm.
[0007] Recently, as the crucible has become larger, the crucible temperature during pulling has tended to become higher. If the temperature of the crucible rises, the viscosity of the glass decreases, and the crucible may be deformed during use. As a countermeasure, it is known that there is a method of coating the surface of the crucible or making the surface contain a crystallization promoter to crystallize the glass at high temperature to increase the strength of the crucible. In addition, it is also known that there is a quartz glass crucible with a three-layer structure in which the outer layer of the crucible is formed by a quartz layer with added Al, the middle layer is formed by a natural quartz layer or a high-purity synthetic quartz layer, and the inner layer is formed by a transparent high-purity synthetic quartz layer (reference patent document 3).
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent Application Publication No. 2020-200199
[0011] Patent Document 2: Japanese Patent Application Publication No. 2009-84114
[0012] Patent Document 3: Japanese Patent Application Publication No. 2000-247778 Summary of the invention
[0013] Technical problem to be solved by the invention
[0014] As described above, the quartz glass crucible is strongly required to have durability to withstand a long crystal pulling process. Although methods of crystallizing the outer surface of the crucible or adding Al are effective, further improvement in the durability of the crucible is required.
[0015] Therefore, an object of the present invention is to provide a quartz glass crucible and a method for manufacturing the same, wherein the thickness of the crystal layer on the outer surface of the crucible when crystallized is thick and can withstand a long crystal pulling process. In addition, another object of the present invention is to provide a method for manufacturing single crystal silicon that can grow long and high-quality single crystal silicon by implementing a long crystal pulling process.
[0016] Solutions for solving technical problems
[0017] In order to solve the above-mentioned problems, the quartz glass crucible for pulling single crystal silicon of the present invention is characterized in that it comprises: a crucible body, which is made of silica glass; and a semi-molten layer, which is formed on the outer side of the outer surface of the crucible body and is formed by a fusion layer of unmolten or semi-molten quartz powder, and a plurality of depressions with a diameter of not less than 0.2 mm and not more than 5.0 mm are formed on the surface of the semi-molten layer, and a part of the depressions is a through hole that penetrates the semi-molten layer and reaches the outer surface of the crucible body, and the density of the through holes is 1 / cm 2 More than 50 pieces / cm 2 the following.
[0018] According to the present invention, the crystallization rate of the outer surface of the crucible can be increased and the crystal layer can be formed thicker. Therefore, the durability of the crucible at high temperatures during crystal pulling can be improved, and a crucible that can withstand a long crystal pulling process can be provided. There are also depressions on the outer surface of the conventional quartz glass crucible, but since the number of deep depressions that penetrate the semi-molten layer and reach the glass layer is small, the crystallization rate of the outer surface is slow, and the thickness of the crystal layer when the outer surface is crystallized is thin. Therefore, the durability of the quartz glass crucible is low and cannot withstand a long crystal pulling process. However, according to the present invention, since the number of depressions that reach the glass layer is large, when the outer surface of the crucible is crystallized, it is easy to crystallize inward, and the thickness of the crystal layer can be increased.
[0019] In the present invention, the thickness of the semi-molten layer is preferably 50 μm or more. When the thickness of the semi-molten layer is 50 μm or more, crystallization of the outer surface of the crucible can be promoted to form a thick crystal layer.
[0020] The quartz glass crucible of the present invention preferably has: a cylindrical side wall; a bottom; and a corner, which is provided between the side wall and the bottom, wherein the wall thickness of the corner is thicker than the wall thickness of the side wall and the bottom, and the formation area of the through hole is provided at least on the entire circumference of the corner. In this way, by distributing the deep depressions penetrating the semi-molten layer at least on the entire circumference of the corner, the crystallization of the corner of the crucible can be promoted, and deformation such as sinking of the crucible can be effectively suppressed.
[0021] Furthermore, the method for manufacturing a quartz glass crucible of the present invention is characterized in that it includes: a step of heating quartz powder accumulated on the inner surface of a rotating mold from the center side of the mold to vitrify it; a step of taking out the quartz glass crucible from the mold after cooling; and a step of honing a semi-molten layer formed by a fusion layer of unmelted or semi-molten quartz powder formed on the outer surface of the quartz glass crucible, wherein the thermal conductivity of the quartz powder forming the natural silica glass layer of the quartz glass crucible is 0.5 W / (m·K) or more and 10 W / (m·K) or less at 750°C.
[0022] According to the present invention, a quartz glass crucible can be manufactured, wherein a semi-molten layer formed by a fusion layer of unmolten or semi-molten quartz powder is formed on the outer surface of a crucible body made of silica glass, a plurality of depressions having a diameter of 0.2 mm or more and 5.0 mm or less are formed on the surface of the semi-molten layer, a part of the depressions is a through hole reaching the outer surface of the crucible body, and the density of the through holes is 1 / cm 2 More than 50 pieces / cm 2 the following.
[0023] In the present invention, the average particle size of the quartz powder is preferably 150 μm or more and less than 400 μm. By using such quartz powder, the manufacturing yield of the quartz glass crucible having the above characteristics can be improved.
[0024] In the present invention, it is preferred that the mold has a cavity that matches the outer shape of the quartz glass crucible, and the opening size of the cavity corresponding to the side wall of the quartz glass crucible is greater than or equal to 1.01 times and less than or equal to 1.15 times the target outer diameter of the side wall. By using such a mold, the manufacturing yield of the quartz glass crucible having the above-mentioned characteristics can be improved.
[0025] The method for producing single crystal silicon of the present invention is characterized in that a polycrystalline silicon raw material is melted in a quartz glass crucible having the above characteristics to generate a silicon melt, and a single crystal silicon is pulled from the silicon melt. According to the present invention, a long crystal pulling process can be performed to grow a long and high-quality silicon crystal.
[0026] Effects of the Invention
[0027] According to the present invention, a quartz glass crucible and a method for manufacturing the same can be provided, wherein the thickness of the crystal layer on the outer surface of the crucible when crystallized is thick and can withstand a long crystal pulling process. In addition, according to the present invention, a method for manufacturing single crystal silicon that can grow long and high-quality single crystal silicon by implementing a long crystal pulling process can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a schematic perspective view showing the structure of a quartz glass crucible according to an embodiment of the present invention.
[0029] Figure 2 It is a schematic side view of the quartz glass crucible according to the present embodiment, the left half is a cross-sectional view, and the right half is an appearance view.
[0030] Figure 3 This is a schematic cross-sectional view of a semi-molten layer having depressions formed therein.
[0031] Figure 4 The schematic cross-sectional views are used to show the state of the semi-molten layer before and after heating of the present invention in comparison with the past, wherein (a) shows the state of the conventional crucible before heating, (b) shows the state of the conventional crucible after heating, (c) shows the state of the crucible of the present invention before heating, and (d) shows the state of the crucible of the present invention after heating.
[0032] Figure 5 It is a schematic diagram showing a method for manufacturing a quartz glass crucible according to an embodiment of the present invention.
[0033] Figure 6It is a diagram for explaining a single crystal pulling step using the quartz glass crucible 1 according to the present embodiment, and is a schematic cross-sectional view showing the structure of a single crystal pulling apparatus.
[0034] Figure 7 This is a graph showing the results of univariate analysis of the deformation amounts of crucible samples 1 to 10 after the heating test. DETAILED DESCRIPTION
[0035] Hereinafter, preferred embodiments of the present invention will be described in detail with reference to the accompanying drawings.
[0036] Figure 1 It is a schematic perspective view showing the structure of a quartz glass crucible according to an embodiment of the present invention.
[0037] like Figure 1 As shown, the quartz glass crucible 1 is a silica glass container for holding silicon melt, and has a cylindrical side wall portion 10a, a bottom 10b provided below the side wall portion 10a, and a corner portion 10c provided between the side wall portion 10a and the bottom 10b. The bottom 10b is preferably a so-called round bottom that is gently curved, but may also be a so-called flat bottom. The corner portion 10c is a portion having a greater curvature than the bottom 10b. The boundary between the side wall portion 10a and the corner portion 10c and the boundary between the corner portion 10c and the bottom 10b can be determined based on the change point of the curvature. Figure 2 The boundary between the side wall portion 10a and the corner portion 10c is slightly offset from the curvature change point, which is different from the description here. Therefore, if you want to slightly correct Figure 2 .
[0038] The caliber (diameter) of the quartz glass crucible 1 varies depending on the diameter of the single crystal silicon ingot pulled out from the silicon melt, but is 18 inches (about 450 mm) or more, preferably 22 inches (about 560 mm), and particularly preferably 32 inches (about 800 mm) or more. The reason is that such a large crucible is used to pull large single crystal silicon ingots with a diameter of 300 mm or more, and it is required that the quality of the single crystal will not be affected even if it is used for a long time.
[0039] The wall thickness of the crucible slightly varies depending on the location, but preferably the wall thickness of the side wall 10a of a crucible larger than 18 inches is 6 mm or more, the wall thickness of the side wall 10a of a crucible larger than 22 inches is 7 mm or more, and the wall thickness of the side wall 10a of a crucible larger than 32 inches is 10 mm or more. This allows a large amount of silicon melt to be stably maintained at a high temperature. The wall thickness of the crucible is preferably thickest at the corner 10c, and the side wall 10a and the bottom 10b are thinner than the corner 10c.
[0040] Figure 2 It is a schematic side view of the quartz glass crucible 1 according to the present embodiment, the left half is a cross-sectional view, and the right half is an appearance view.
[0041] like Figure 2 As shown, the quartz glass crucible 1 comprises a crucible body 10 made of silica glass and a semi-molten layer 13 formed on the outer surface 10o of the crucible body 10. The crucible body 10 is a double-layer structure having a transparent layer 11 (bubble-free layer) containing no bubbles and a bubble layer 12 (opaque layer) containing a large number of tiny bubbles, and the semi-molten layer 13 is arranged on the outer side of the bubble layer 12. A crystallization accelerator may be coated or added to the outer surface of the semi-molten layer 13.
[0042] The transparent layer 11 is a glass layer constituting the inner surface 10i of the crucible body 10 in contact with the silicon melt, and is provided to prevent the yield of the single crystal silicon from being reduced due to bubbles in the silica glass. The inner surface 10i of the crucible is melted due to the reaction with the silicon melt, so the bubbles near the inner surface of the crucible cannot be sealed in the silica glass, and there is a possibility that the bubbles will burst due to thermal expansion, resulting in the peeling of the crucible fragments (silicon dioxide fragments). When the crucible fragments released into the silicon melt are transported to the growth interface of the single crystal silicon by the convection of the melt and are incorporated into the single crystal silicon, it becomes a cause of dislocation of the single crystal. In addition, when the bubbles released into the silicon melt float up and reach the solid-liquid interface and are incorporated into the single crystal, it becomes a cause of pinholes in the single crystal silicon.
[0043] The transparent layer 11 does not contain bubbles, which means that the bubble content and bubble size are such that the single crystal rate is not reduced by the bubbles. The bubble content is, for example, 0.1 vol% or less, and the bubble diameter is, for example, 100 μm or less.
[0044] The thickness of the transparent layer 11 is preferably 0.5 to 10 mm, and is set to an appropriate thickness at each part of the crucible so that the transparent layer 11 does not completely disappear due to melting loss in the crystal pulling process, thereby exposing the bubble layer 12. The transparent layer 11 is preferably provided on the entire crucible from the side wall portion 10a to the bottom 10b of the crucible, but the transparent layer 11 may be omitted at the upper end of the crucible that does not contact the silicon melt.
[0045] The bubble layer 12 is a main glass layer of the crucible body 10 located outside the transparent layer 11, and is provided to improve the heat preservation of the silicon melt in the crucible and to disperse the radiation heat from the heater of the single crystal pulling device to heat the silicon melt in the crucible as uniformly as possible. Therefore, the bubble layer 12 is provided on the entire crucible from the side wall portion 10a to the bottom 10b.
[0046] The bubble content of the bubble layer 12 is higher than that of the transparent layer 11, and is preferably greater than 0.1 vol% and less than 5 vol%. The reason is that if the bubble content of the bubble layer 12 is less than 0.1 vol%, the heat preservation function required of the bubble layer 12 cannot be exerted. In addition, when the bubble content of the bubble layer 12 exceeds 5 vol%, there is a possibility that the crucible is deformed due to the thermal expansion of the bubbles, resulting in a decrease in the single crystal yield, and the heat conductivity becomes insufficient. From the perspective of the balance between heat preservation and heat conductivity, the bubble content of the bubble layer 12 is particularly preferably 1 to 4 vol%. In addition, the bubble content is a value measured on an unused crucible under room temperature.
[0047] The semi-molten layer 13 is a layer formed by cooling a part of the quartz powder as the raw material of the crucible in an incompletely molten state (semi-molten state) on the outer surface of the crucible. The semi-molten layer 13 has an undulating surface and a thickness of 50 to 2000 μm. When manufacturing the crucible, the steeper the temperature gradient near the outer surface, the thinner the thickness of the semi-molten layer 13, and the gentler the temperature gradient, the thicker the thickness of the semi-molten layer 13. Since the temperature gradient is different for each part of the crucible, the thickness of the semi-molten layer 13 is also slightly different for each part of the crucible. The thickness of the semi-molten layer 13 can be obtained by measuring the cross section of a sample cut out from the crucible.
[0048] Whether a semi-molten layer 13 is formed on the outer surface of the crucible can be determined by whether a halo pattern of a fuzzy diffraction image peculiar to amorphous and a peak indicating crystallinity are mixed when the outer surface of the crucible is measured by X-ray diffraction. In the case where the measurement object is a crystal layer, a peak indicating crystallinity is detected, but a halo pattern of a fuzzy diffraction image is not detected. If the semi-molten layer 13 is removed, the surface of the glass is exposed, so the peak cannot be detected.
[0049] A plurality of depressions 14 are formed on the surface of the semi-molten layer 13 (the outer surface of the crucible). The depressions 14 play a role in promoting crystallization of the outer surface of the crucible. In particular, by forming more deep depressions 14 that penetrate the semi-molten layer 13 and reach the glass layer 15, a thick crystal layer can be formed on the outer surface of the crucible.
[0050] The depression 14 is a depression that can be easily confirmed and identified visually, and has a concave shape that is significantly different from the surroundings. The diameter of the depression 14 is 0.2 to 5.0 mm, more preferably 0.3 to 2.0 mm, and even more preferably 0.5 to 1.0 mm. In the case of less than 0.2 mm, crystallization will not proceed to the thickness of the crystal layer that can suppress the deformation of the crucible. On the other hand, in the case of exceeding 5.0 mm, the outer surface of the crucible is over-crystallized and cracks in the crystal layer are likely to occur, causing deformation of the crucible. The opening shape of the depression is mostly elliptical, and the diameter at this time is defined as the maximum diameter of the opening.
[0051] The depth of the depression 14 is 50 to 2100 μm, more preferably 50 to 1000 μm, and even more preferably 50 to 300 μm. When the depth of the depression 14 is less than 50 μm, crystallization will not proceed to a thickness of the crystal layer that can suppress the deformation of the crucible. On the other hand, when the depth exceeds 2100 μm, the outer surface of the crucible is excessively crystallized and cracks are easily generated in the crystal layer, which causes the deformation of the crucible.
[0052] Figure 3 This is a schematic cross-sectional view of a semi-molten layer having depressions formed therein.
[0053] like Figure 3 As shown, a portion of the plurality of depressions 14 is a through hole 14d that penetrates the semi-molten layer 13, and the bottom thereof reaches the glass layer 15 (i.e., the bubble layer 12) constituting the crucible body 10, and some of the through holes even reach the inside of the glass layer 15. The glass layer 15 is exposed through the depressions 14, so that heat is easily transferred to the glass layer 15, and the glass layer 15 is easily crystallized. If the crystallization speed of the glass layer 15 is compared with that of the semi-molten layer 13, the crystallization speed of the glass layer 15 is faster. Since a portion of the depressions 14 reaches the glass layer 15, when crystallization occurs on the outer surface of the crucible, it is easy to crystallize inward, and the thickness of the crystal layer can be increased.
[0054] The density of the deep depressions 14 (through holes 14d) penetrating the semi-molten layer 13 is preferably 1 to 50 / cm 2 , more preferably 2 to 30 pieces / cm 2 , more preferably 5 to 20 pieces / cm 2 The density of the deep depressions 14 penetrating the semi-molten layer 13 is less than 1 / cm 2 In the case of more than 50 pieces / cm, crystallization will not proceed to a crystal layer thickness that can suppress the deformation of the crucible. 2 In the case of excessive crystallization, the outer surface of the crucible is easily cracked, which causes deformation of the crucible.
[0055] The thickness d of the semi-molten layer 13 is 1Less than the maximum depth d of the depression 14 2 . The preferred range of the thickness of the semi-molten layer 13 is 50 to 2000 μm, more preferably 100 to 1000 μm, and further preferably 100 to 500 μm. When the thickness of the semi-molten layer 13 is less than 50 μm, crystallization will not proceed to the thickness of the crystal layer that can suppress the deformation of the crucible. On the other hand, when it exceeds 2000 μm, the outer surface peeling caused by the difference in thermal expansion coefficient between the semi-molten layer 13 and the glass layer 15 occurs during the single crystal silicon pulling process, and the probability of crucible deformation becomes high.
[0056] It is preferred that the through holes 14d are provided at least at the corner 10c of the crucible and distributed over the entire circumference of the corner 10c. It is further preferred that the through holes 14d are provided from the lower portion 10a of the side wall 10a to the lower portion 10a of the side wall 10a. 2 Thus, by providing a plurality of through holes 14d at the corners 10c of the crucible, the crystallization of the outer surface of the crucible can be promoted to improve the strength of the crucible, and in particular, the buckling / sinking of the corners of the crucible can be effectively suppressed.
[0057] Corner 10c is a part that easily becomes hot and is prone to buckling / sinking. Recently, due to the frequent multiple pulling operations, the crucible is exposed to high temperature for a long time, so buckling / sinking of the corners is prone to occur. If buckling / sinking of the crucible occurs, the probability of tiny crucible pieces (silicon dioxide pieces) peeling off from the inner surface of corner 10c becomes higher. When the crucible pieces are transported to the growth interface of single crystal silicon by melt convection and incorporated into the single crystal silicon, they become the cause of dislocation of the single crystal. However, as described above, when the crystallization of the corners of the crucible is promoted to improve the strength of the crucible, the peeling of tiny silicon dioxide pieces can be suppressed, thereby preventing the dislocation of the single crystal silicon.
[0058] The formation area of the recess 14 may be provided at the upper portion 10a of the side wall portion 10a. 1 When the side wall 10a or the bottom 10b is formed with the depression 14, the depression 14 may be a deep depression (through hole 14d) reaching the glass layer 15 or a shallow depression (non-through hole) not reaching the glass layer 15.
[0059] Figure 4 It is a schematic cross-sectional view showing the states of the semi-molten layer 13 before and after heating of the present invention in comparison with the related art.
[0060] like Figure 4 As shown in (a), there is also a depression 14 in the semi-molten layer 13 of the conventional quartz glass crucible, but the depth of the depression 14 is shallow and does not reach the glass layer 15. Figure 4As shown in (b), even when the outer surface of the crucible is crystallized by heating in the crystal pulling step, the crystal layer 16 cannot be formed thick.
[0061] On the other hand, Figure 4 As shown in (c), most of the depressions 14 formed in the semi-molten layer 13 of the quartz glass crucible of the present invention reach the glass layer 15, and part of the depressions 14 further extend deeper than the surface of the glass layer 15, so that heat is easily transferred to the deep part of the crucible. Figure 4 As shown in (d), when the outer surface of the crucible is crystallized by heating in the crystal pulling step, the crystal layer 16 can be formed thicker, thereby improving the strength of the crucible.
[0062] In order to prevent silicon melt from being contaminated, the silica glass constituting the transparent layer 11 is preferably of high purity. Therefore, the quartz glass crucible 1 preferably has a double-layer structure of a synthetic silica glass layer (synthetic layer) formed of synthetic quartz powder (synthetic silica powder) and a natural silica glass layer (natural layer) formed of natural quartz powder. Synthetic quartz powder can be formed by silicon tetrachloride (SiCl 4 ) by gas phase oxidation (dry synthesis method) or hydrolysis of silicon alkoxide (sol-gel method), and is preferably used as a raw material for forming the inner surface of a crucible in contact with a silicon melt. In addition, natural quartz powder can be produced by crushing a natural mineral with α-quartz as the main component into granules. Natural quartz powder is a naturally produced crystalline quartz powder, and is preferably used as the main raw material of a crucible because it is relatively cheap.
[0063] The double-layer structure of the synthetic silica glass layer and the natural silica glass layer can be manufactured as follows: natural quartz powder is deposited along the inner surface of the crucible manufacturing mold, synthetic quartz powder is deposited thereon, and these raw quartz powders are melted by Joule heat obtained by arc discharge. The arc melting process forms a transparent layer 11 by removing bubbles by strong vacuuming from the outside of the quartz powder deposited layer, and the bubble layer 12 is formed by stopping or weakening the vacuuming. Therefore, the boundary surface between the synthetic silica glass layer and the natural silica glass layer is not necessarily consistent with the boundary surface between the transparent layer 11 and the bubble layer 12, but the synthetic silica glass layer is preferably thick enough not to completely disappear due to the melting loss of the inner surface of the crucible in the single crystal pulling process, like the transparent layer 11.
[0064] The quartz glass crucible 1 of the present embodiment can be produced by a so-called rotational mold method.
[0065] Figure 5 It is a schematic diagram showing a method for manufacturing a quartz glass crucible 1 according to an embodiment of the present invention.
[0066] like Figure 5As shown, in the manufacture of the quartz glass crucible 1 based on the rotational mold method, a mold 20 having a cavity matching the outer shape of the crucible is used. The inner diameter of the mold 20 is preferably 1 to 15% wider than the target outer diameter of the side wall of the crucible. That is, the opening size of the cavity is preferably 1.01 to 1.15 times the target diameter of the crucible. In this way, by setting the opening size of the mold cavity wider than before, the diameter of the completed crucible can be made consistent with the target diameter.
[0067] Next, natural quartz powder 21a and synthetic quartz powder 21b are sequentially filled along the inner surface 20i of the rotating mold 20 to form a quartz powder accumulation layer 21. The quartz powder adheres to the inner surface 20i of the mold 20 due to centrifugal force, and stays at a constant position in this state, maintaining the shape of the crucible. The thickness (height) of the quartz powder accumulation layer 21 is thicker than the target wall thickness of each part of the crucible, preferably 1.06 to 1.1 times the target wall thickness.
[0068] The thermal conductivity of the natural quartz powder 21a is preferably 0.2 to 10 W / (m·K) at 750°C, more preferably 0.3 to 1.0 W / (m·K), and further preferably 0.45 to 0.6 W / (m·K). When using a raw material powder with a thermal conductivity within this range, it is easy to form multiple depressions with a desired depth on the semi-molten layer 13 formed on the outer surface of the crucible. If the thermal conductivity is less than 0.2 W / (m·K), no depressions will occur. On the other hand, when the thermal conductivity exceeds 10 W / (m·K), excessive depressions will occur, and the outer surface of the crucible will be excessively crystallized during the crystal pulling process, and cracks will easily occur in the crystal layer, which will cause deformation of the crucible. In addition, since the melting of the raw material powder does not proceed, the outer diameter of the crucible becomes larger, resulting in the problem that the crucible cannot enter the carbon base used when pulling single crystal silicon.
[0069] The average particle size of the natural quartz powder 21a is preferably 150 to 400 μm. If the average particle size is less than 150 μm, the crucible cannot be removed from the mold due to excessive melting of the raw material powder. On the other hand, if the average particle size exceeds 400 μm, the melting of the raw material powder does not proceed, the outer diameter of the crucible becomes larger, and there is a problem that it cannot be set on the carbon base used when pulling single crystal silicon.
[0070] Next, an arc electrode 22 is placed in the mold 20 to arc melt the quartz powder accumulation layer 21 from the inside of the mold 20. Specific conditions such as heating time and heating temperature can be appropriately determined in consideration of conditions such as the properties of the quartz powder and the size of the crucible.
[0071] If quartz powder with a thermal conductivity of 0.2 to 10 W / (m·K) at 750°C is used, even if the quartz powder accumulation layer 21 is heated, the heat will not stay in the accumulation layer 21 and will easily escape, so the outer diameter of the crucible tends to be less likely to become thicker. However, as described above, by increasing the opening size of the cavity of the mold 20 to thicken the accumulation layer 21, the heat can easily stay in the accumulation layer 21 and the outer diameter of the crucible can be set to the desired diameter. As described above, the thickness of the quartz powder accumulation layer 21 is preferably 1.5 to 3.0 times the wall thickness of the crucible. In the case of thickening the quartz powder accumulation layer 21, the mold 20 needs to be rotated at a higher speed.
[0072] During the arc melting process, the amount of bubbles in the molten silica glass is controlled by vacuuming the quartz powder accumulation layer 21 through a plurality of vent holes 20a provided on the inner surface 20i of the mold 20. Specifically, at the start of arc melting, the quartz powder accumulation layer 21 is vacuumed to form a transparent layer 11, and after the transparent layer 11 is formed, the vacuuming is stopped or the suction force is weakened to form a bubble layer 12.
[0073] The arc heat is slowly transferred from the inside to the outside of the quartz powder accumulation layer 21 and melts the quartz powder. Therefore, by changing the decompression conditions at the time when the quartz powder starts to melt, the transparent layer 11 and the bubble layer 12 can be separately produced. That is, if the decompression melting is performed to increase the decompression at the time of melting the quartz powder, the arc atmosphere gas will not be sealed in the glass, so the fused silica becomes a silica glass without bubbles. In addition, if the normal melting (atmospheric pressure melting) is performed to reduce the decompression at the time of melting the quartz powder, the arc atmosphere gas will be sealed in the glass, so the fused silica becomes a silica glass containing a large number of bubbles.
[0074] After that, the arc melting is terminated and the crucible is cooled. In particular, by terminating the arc heating before the quartz powder near the inner surface of the mold 20 is completely melted, the mold 20 and the glass layer can be prevented from being closely attached, and the crucible can be easily removed from the mold 20. In addition, by terminating the arc heating before the quartz powder near the inner surface of the mold 20 is completely melted, a semi-melted layer 13 formed by a fused layer of unmelted or semi-melted quartz powder can be formed on the outer surface of the crucible.
[0075] Through the above method, the quartz glass crucible 1 is completed in which the transparent layer 11, the bubble layer 12 and the semi-molten layer 13 are sequentially provided from the inside to the outside of the crucible.
[0076] Next, after the crucible is shaped into a predetermined shape by cutting the edge, the outer surface of the crucible is honed to remove the quartz powder residue. In the honing process, it is preferred to spray high-pressure pure water to remove the excess quartz powder. Through the honing process, the depression 14 on the surface of the semi-molten layer 13 can be revealed.
[0077] After that, the crucible is cleaned with a cleaning solution and further rinsed with pure water. The cleaning solution is preferably prepared by diluting semiconductor-grade or higher hydrofluoric acid with pure water having a TOC of ≤ 2 ppb to 10 to 40 wt%. In this way, a series of manufacturing steps of the quartz glass crucible 1 are completed.
[0078] As described above, the quartz glass crucible 1 of the present embodiment includes a crucible body 10 made of silica glass and a semi-molten layer 13 formed on the outer surface 10o of the crucible body 10, and a plurality of depressions 14 are formed on the surface of the semi-molten layer 13. Part of the depressions 14 reaches the crucible body 10, thereby promoting crystallization of the outer surface of the crucible and forming a thicker crystal layer, thereby improving the durability of the crucible.
[0079] Furthermore, in the method for manufacturing the quartz glass crucible 1 of the present embodiment, since the quartz glass crucible is manufactured using quartz powder having a relatively high thermal conductivity of 0.2 W / (m·K) or more and 10 W / (m·K) or less at 750°C, a quartz glass crucible having a plurality of deep depressions formed on the surface of the semi-molten layer can be manufactured.
[0080] Figure 6 It is a diagram for explaining a single crystal pulling step using the quartz glass crucible 1 according to the present embodiment, and is a schematic cross-sectional view showing the structure of a single crystal pulling apparatus.
[0081] like Figure 6 As shown, a single crystal pulling device 30 is used in the pulling process of single crystal silicon based on the CZ method. The single crystal pulling device 30 includes: a water-cooled chamber 31; a quartz glass crucible 1, which holds a silicon melt in the chamber 31; a carbon susceptor 32, which holds the quartz glass crucible 1; a rotating shaft 33, which supports the carbon susceptor 32 rotatably and elevatingly; an axis driving mechanism 34, which drives the rotating shaft 33 to rotate and elevate; a heater 35, which is arranged around the carbon susceptor 32; a substantially cylindrical heat shielding member 36, which is arranged above the quartz glass crucible 1; a single crystal pulling wire 38, which is arranged above the quartz glass crucible 1 and is coaxial with the rotating shaft 33; and a winding mechanism 39, which is arranged above the chamber 31.
[0082] The chamber 31 is composed of a main chamber 31a and an elongated cylindrical crystal pulling chamber 31b connected to the upper opening of the main chamber 31a. The quartz glass crucible 1, the carbon susceptor 32 and the heater 35 are arranged in the main chamber 31a. A gas inlet 31c for introducing an inert gas (purge gas) such as argon or a dopant gas into the main chamber 31a is arranged at the upper part of the crystal pulling chamber 31b, and a gas exhaust port 31d for exhausting the atmosphere gas in the main chamber 31a is arranged at the lower part of the main chamber 31a.
[0083] The carbon susceptor 32 is used to maintain the shape of the quartz glass crucible 1 softened at high temperature, and holds the quartz glass crucible 1 in a manner of covering it. The quartz glass crucible 1 and the carbon susceptor 32 constitute a double-structure crucible that supports silicon melt in the chamber 31.
[0084] The carbon susceptor 32 is fixed to the upper end of the rotating shaft 33 , and the lower end of the rotating shaft 33 is connected to a shaft driving mechanism 34 that penetrates the bottom of the chamber 31 and is provided outside the chamber 31 .
[0085] The heater 35 is used to melt the polycrystalline silicon raw material filled in the quartz glass crucible 1 to generate the silicon melt 2 and to maintain the molten state of the silicon melt 2. The heater 35 is a resistance heating carbon heater and is provided so as to surround the quartz glass crucible 1 in the carbon susceptor 32.
[0086] The heat shielding component 36 is a graphite component that covers the area above the silicon melt 2 except for the pulling path of the single crystal silicon 3. It is provided to suppress the temperature variation of the silicon melt 2 and form an appropriate hot zone near the solid-liquid interface, and to prevent the radiation heat from the heater 35 and the quartz glass crucible 1 from heating the single crystal silicon 3.
[0087] A circular opening larger than the diameter of the single crystal silicon 3 is formed at the center of the lower end of the heat shielding member 36. Since the diameter of the opening 17a of the heat shielding member 36 is smaller than the diameter of the quartz glass crucible 1, the lower end of the heat shielding member 36 is located inside the quartz glass crucible 1. Therefore, even if the upper end of the edge of the quartz glass crucible 1 rises above the lower end of the heat shielding member 36, the heat shielding member 36 will not interfere with the quartz glass crucible 1.
[0088] The heat shielding member 36 also functions as a gas rectifying member for rectifying the gas flow near the surface of the silicon melt 2. As the single crystal silicon 3 grows, the amount of melt decreases, and the liquid level in the quartz glass crucible 1 slowly decreases. However, by slowly raising the quartz glass crucible 1, the distance (gap value) from the liquid surface of the silicon melt 2 to the lower end of the heat shielding member 36 can be maintained constant, and the flow rate of the gas flowing near the melt surface can be kept constant. Therefore, the temperature change of the silicon melt 2 can be suppressed and the evaporation amount of the dopant from the silicon melt 2 can be controlled, and the stability of the crystal defect distribution, oxygen concentration distribution, resistivity distribution, etc. in the pulling axis direction of the single crystal can be improved.
[0089] The winding mechanism 39 is disposed above the crystal pulling chamber 31b, and the wire 38 extends downward from the winding mechanism 39 through the crystal pulling chamber 31b, and the front end of the wire 38 reaches the internal space of the main chamber 31a. The figure shows the state in which the single crystal silicon 3 is suspended on the wire 38 during the growth process. When the single crystal silicon 3 is pulled, the quartz glass crucible 1 and the single crystal silicon 3 are rotated respectively, and the wire 38 is slowly pulled to grow the single crystal silicon 3.
[0090] During the single crystal pulling process, the quartz glass crucible 1 softens, but the outer surface of the crucible is crystallized, which increases the strength of the crucible and suppresses deformation such as sinking and internal collapse of the crucible. Therefore, it is possible to prevent the liquid level of the silicon melt 2 from changing drastically due to the change in the volume of the crucible, or to prevent the crucible from contacting the heat shielding member 36.
[0091] As mentioned above, although the preferred embodiment of the present invention has been described, the present invention is not limited to the above-mentioned embodiment, and various modifications can be made without departing from the gist of the present invention, and these are naturally included in the scope of the present invention.
[0092] For example, in the above embodiment, the semi-molten layer 13 is formed on the entire crucible from the bottom 10b of the crucible to the upper end of the side wall portion 10a, but the semi-molten layer 13 may not be formed on the bottom 10b or near the upper end of the edge.
[0093] Example
[0094] Samples 1 to 10 of quartz glass crucibles manufactured by the rotational mold method were prepared, and the diameter (mm) of the depressions formed on the entire circumference of these corners, the depth (μm) of the depressions, and the density (number / cm) of deep depressions (through holes) reaching the glass layer were evaluated. 2 ). The diameter and depth of the depression were measured using a surface roughness measuring machine manufactured by Mitutoyo Corporation: SURFTEST SJ-301. The measurement speed was 0.5 mm / sec. Regarding the diameter of the depression, a sample was cut out from a quartz crucible and measured. Regarding the arrival position of the front end of the depression, a fluorescent lamp was irradiated from the inner surface side of the quartz crucible and visually determined from the outer surface side of the crucible. That is, the diameter and depth of the depression were measured mechanically, but the evaluation of whether the front end of the depression reached the glass layer was performed by visual confirmation. The measurement results are shown in Table 1. Samples 1 to 6 are comparative examples, and samples 7 to 10 are embodiments.
[0095] [Table 1]
[0096]
[0097] Next, the heat deformation resistance of the quartz glass crucible samples 1 to 10 was evaluated. In the evaluation of the heat deformation resistance, the samples were placed in a test furnace and kept at 1500°C for 50 hours, then the crucibles were taken out and evaluated for deformation. Specifically, the heat deformation resistance was quantitatively evaluated by measuring the change in the crucible height (deformation) before and after the test. The evaluation results of the heat deformation resistance are also shown in Table 1.
[0098] As can be seen from Table 1, in crucible samples 1 to 6, changes in crucible heights were observed and the crucibles sank significantly. On the other hand, in crucible samples 7 to 10, no significant sinking of the crucibles was observed.
[0099] Figure 7 This is a graph showing the results of univariate analysis of the deformation of crucible samples 1 to 10 after a heating test at 1500° C. for 50 hours.
[0100] like Figure 7 As shown, it was confirmed that the deformation amount of crucible samples 1 to 6 was about 7.9 to 10.3 mm, while the deformation amount of crucible samples 7 to 10 was about 2.3 to 3.4 mm, and the sinking amount of crucible samples 7 to 10 was smaller.
[0101] Description of Reference Numerals
[0102] 1-quartz glass crucible, 2-silicon melt, 3-single crystal silicon, 10-crucible body, 10a-side wall, 10a 1 Upper part of the side wall, 10a 2 The lower part of the side wall, 10b-bottom, 10c-corner, 10i-inner surface, 10o-outer surface, 11-transparent layer, 11-quartz crucible, 12-bubble layer, 13-semi-molten layer, 14-depression, 14d-through hole (deep depression), 15-glass layer, 16-crystal layer, 17a-opening, 20-mold, 20a-vent, 20i-inner surface of the mold, 21-deposited layer, 21a-natural quartz powder, 21b-synthetic quartz powder, 22-arc electrode, 30-single crystal pulling device, 31-chamber, 31a-main chamber, 31b-crystal pulling chamber, 31c-gas inlet, 31d-gas outlet, 32-carbon base, 33-rotating axis, 34-axis driving mechanism, 35-heater, 36-heat shielding component, 38-single crystal pulling wire, 39-winding mechanism.
Claims
1. A quartz glass crucible, which is a quartz glass crucible for pulling single crystal silicon, It is characterized in that have: A crucible body made of silica glass; and a semi-molten layer formed outside the outer surface of the crucible body and formed by a fusion layer of unmolten or semi-molten quartz powder, A plurality of depressions having a diameter of 0.2 mm or more and 5.0 mm or less and a depth of 50 μm or more are formed on the surface of the semi-molten layer, A portion of the depression is a through hole that penetrates the semi-molten layer and reaches the outer surface of the crucible body, and the density of the through holes is 1 / cm 2 More than 50 pieces / cm 2 the following.
2. The quartz glass crucible according to claim 1, in, The semi-molten layer has a thickness of 50 μm or more.
3. The quartz glass crucible according to claim 1, comprising: a cylindrical side wall portion; bottom; and A corner portion is disposed between the side wall portion and the bottom portion, The wall thickness of the corner portion is thicker than the wall thickness of the side wall portion and the bottom portion, The through hole formation region is provided at least over the entire circumference of the corner portion.
4. A method for producing single crystal silicon, which is a method for producing single crystal silicon based on the Czochralski method, It is characterized in that A polycrystalline silicon raw material is melted in a quartz glass crucible according to any one of claims 1 to 3 to generate a silicon melt, and a single crystal silicon is pulled out from the silicon melt.
Citation Information
Patent Citations
Quartz glass crucible, its production and pulling up of silicon single crystal using the same
JP2000247778A
Quartz glass crucible for pulling silicon single crystal and its manufacturing method
JP2009084114A
Quartz glass crucible and method for manufacturing the same
JP2020200199A